The Effect of Appropriate Placement of Employees with Disabilities on Work Productivity - Lubna Anwar Sadat; Ilyu ‘Ainun Najie (Syntax Corporation, 2023)
Disabled employee placement is an increasingly important topic in the context of employment equity. The problem of imbalance or mismatch in the placement of employees with disabilities in the work environment can affect work productivity and career continuity. The purpose of this study is to analyze the effect of appropriate placement of employees with disabilities on work productivity. This research uses quantitative methods. Data were collected through questionnaires distributed to employees with disabilities in various companies in Indonesia. The population in this study were employees with disabilities in Indonesia. The sampling technique was carried out using random sampling technique. The data collected was analyzed using simple linear regression statistical tests. The results showed that appropriate placement has a positive influence on the work productivity of employees with disabilities. Disabled employees who are placed in positions that match their abilities have higher work productivity than disabled employees who are placed in inappropriate positions. Therefore, companies need to place employees with disabilities carefully and pay attention to their abilities.